Research Trends in School Excellent Model (SEM): The Future Insights for Islamic Education Assessment - Khoiriyah, Siti; Faizin, Moh; Asror, Moh; Kusaeri, Kusaeri (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
A School Excellent Model (SEM) is a concept of excellent school management in which there are interesting programs that can lead to the goal of quality education. Education needs in the digital era are increasingly complex, requiring practitioners to adapt and have diverse skills and competencies. It is intended to achieve the goal of quality education by one of the goals of the Sustainable Development Goals (SDGs). This research uses a type of literature review in the form of a Systematic Literature Review (SLR) of articles indexed by Scopus about the School Excellent Model from 2015 to 2022 that have gone through a process of screening, eligibility, extraction, and inclusion criteria. The results of the research literature review on SEM from 2015 to 2022 are 1) mapping related studies; a. competence of an educator in managing learning, conducting assessments or assessments, and integrating technology in learning. b. competence of a leader (principal) in managing institutions, resources, and teacher coaching. c. The need for relationships and cooperation with school partners such as the government, parents, and the community is urgent. d. Innovation and continuous improvement of education. 2) From mapping the results of research studies on SEM, several things were found that can be used as insights into Islamic religious education in Indonesia, including the development of the quality of Islamic religious educators who are technologically sensitive, competent, and adaptive and can formulate assessment techniques for quality learning (self-assessment, formative and assessment ). Development of leadership skills and communication skills for education managers and implementers.